The Effectiveness of Internal Control in Preventing Accounting Fraud in Financial Companies - Ilmiha, Jalilah; Suboh, Amerruddin Shah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the effectiveness of internal control in preventing accounting fraud in financial companies. The main focus of this research is on the components of the control environment, risk assessment, control activities, and information and communication. The research method used is descriptive with a qualitative approach, involving in-depth interviews, observation and documentation studies. The research results show that a strong control environment and comprehensive risk assessment are very important in reducing the risk of accounting fraud. Effective control activities, such as segregation of duties, transaction authorization, document verification, and account reconciliation, combined with reliable information systems and good internal communications, can prevent fraud and ensure the integrity of financial reports. The conclusion of this research confirms that strong integration between various internal control components is the key to creating an effective control system for preventing accounting fraud in financial companies.